2022
DOI: 10.4103/2211-5056.362601
|View full text |Cite
|
Sign up to set email alerts
|

Central serous chorioretinopathy

Abstract: Central serous chorioretinopathy (CSC) has remained an enigmatic disease since its initial description by Von Graefe. Over the years, multiple risk factors have been recognized: these include psychological stress, behavioral traits, and corticosteroids. The basic pathophysiology of CSC involves choroidal thickening, vascular congestion, altered choroidal blood flow (ChBF), and choroidal hyperpermeability, leading to retinal pigment epithelium decompensation and subsequent neurosensory detachment. Multiple orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 142 publications
0
4
0
Order By: Relevance
“…Recent studies have demonstrated an increased vulnerability of choroidal blood flow to vascular variations in patients with CSCR 13 , 14 . Disturbances of the endocrinal system can lead to a dysregulation of the vascular tone and could therefore contribute to the pathogenesis of CSCR 15 . A direct causative relation of a hyperparathyroidism or additive aggravating effect of an imbalance in the hypothalmic-pituary-adrenal and/or renin-angiotension-aldosterone axes were discussed in our case.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated an increased vulnerability of choroidal blood flow to vascular variations in patients with CSCR 13 , 14 . Disturbances of the endocrinal system can lead to a dysregulation of the vascular tone and could therefore contribute to the pathogenesis of CSCR 15 . A direct causative relation of a hyperparathyroidism or additive aggravating effect of an imbalance in the hypothalmic-pituary-adrenal and/or renin-angiotension-aldosterone axes were discussed in our case.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, this causes retinal neuroepithelial detachment in the macular area combined with focal retinal pigment epithelial detachment. Patients experience several clinical manifestations, including mild visual loss, darkening of vision, hue changes, and central relative dark areas [11][12][13][14]. The incidence of CSC differs significantly between genders and occurs predominantly in men and rarely in women.…”
Section: Discussionmentioning
confidence: 99%
“…In recent times, it has been acknowledged that inflammation plays a crucial role in the advancement and onset of CSC. Hence, targeting inflammation through molecular markers could be a promising treatment strategy for CSC( Jain et al, 2022 ). The inflammatory process of CSC involves a dynamic interplay between cytokines, chemokines, and adhesion molecules.…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%
“…In recent times, it has been acknowledged that inflammation plays a crucial role in the advancement and onset of CSC. Hence, targeting inflammation through molecular markers could be a promising treatment strategy for CSC (Jain et al, 2022).…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%